Shear Strengthening of RC Beams with FRCM Technique - M.A. Kadhim, Majid; Hadi Adheem, Ali; Altaee, Mohammed J (International Journal of Engineering and Technology, 2018)
Nowadays, utilizationof Fibre Reinforced Polymer (FRP) in rehabilitation and strengthening of Reinforced Concrete (RC) beams is commonly used with a proper type of epoxy. Fabric Reinforced Cementitious Material (FRCM) presentsan alternative technique instead of the traditional epoxy. This paper investigates the shear performance of RC beamsusing FRCM strengthening.Finite Element method was adopted in modelingthe FRCM strengtheningfor RC beams in shear using ANSYS software with nonlinear and 3D analysis. In the beginning, the FE model was verified through comparing with the tests in the literature in terms of load-mid span deflection response, ultimate load, strain readings of reinforcement at mid-spanand the mode of failure. It was found that the FE model was capable to capture the behavior of FRCM strengthened RC beams with a high level of accuracy. This validated model has been employed later in studying some of parameters which have a potential effecton efficiency of this technique such as concrete compressive strength, number of fiber layers, and the arrangement of the fiber. Generally, it was found that the concrete compressive with high strength has significant impact in increase the efficiencyof FRCM strengthening system.Â